OS 05-01 PROX1 GENE CC GENOTYPE AS A MAJOR DETERMINANT OF EARLY ONSET OF T2D AND CARDIOVASCULAR COMPLICATIONS IN SLAVIC SUBJECTS FROM ADVANCE STUDY. (September 2016) - Hamet, Pavel; Haloui, Mounsif; Harvey, François; Marois-Blanchet, François-Christophe; Simon, Paul; Raelson, John; Phillips, Michael; Chalmers, John; Woodward, Mark; Marre, Michel; Harrap, Stephen; Tremblay, Johanne
Abstract : Objective: We have previously reported distinct genetic architectures of renal impairment in T2D patients of Slavic and Celtic origins participating in the ADVANCE trial (J Hypertens. 2015 Jun;33 Suppl 1:e3). Further analysis suggests that the major driver of the difference in the prevalence of T2D complications between Slavic and Celtic groups is due to an earlier onset of diabetes in Slavic patients. In an attempt to distinguish between environmental and genetic factors on age of onset of diabetes, we have determined the age of onset of T2D in Slavic subjects living in Celtic countries and confirmed the same earlier onset (-2 years) in these subjects, notwithstanding their living environment. Design and Method: We performed GWAS analyses of age of onset of T2D in 3500 T2D patients from ADVANCE trial. Analyses were done for Celtic and Slavic groups separately and combined. Results: 7 loci are associated to age of onset of T2D in patients of both Celtic and Slavic origins, including HDAC9 gene (rs1128745). 9 loci are selectively associated to this phenotype in patients of Celtic origin, including the Il23R (rs1273974) while 9 different loci are associated to it in Slavic patients only. Among the latter, PROX1/PROX1-AS1 genes (rs340841) has the highest effect size. SNP rs 340841 homozygous CC genotype is associated with 2 years earlier onset of T2D in Slavic patients living in Slavic countries or in Celtic countries. This locus is also associated with eGFR decline in Slavic, with macroalbuminuria and hypertension in all ADVANCE subjects of Caucasian origin and with Interleukin-6 levels at baseline. In recent literature search we found that PROX1 gene has been associated with abnormalities of glucose metabolism and risk of diabetes with variations depending on ethnicity. Conclusions: We conclude that fine granularity of distinction in geo-ethic background assist in resolution of clinically relevant genetic contribution to cardiovascular complication in T2D.